If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3x = 0 Combine like terms: 7x + -3x = 4x 4x = 0 Solving 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '4'. x = 0 Simplifying x = 0
| 16(x+.5)(x+.5)=1 | | [3X+2]=[X-1] | | X^2-2x=33 | | y=3x^3+10x^2+8x | | x(6x-20)=(x+10)(x+10) | | 3+4a=15 | | y^4-4y^2+4y-1=0 | | 5(x+6)+2(2x-9)=39 | | 16=3.14x^2-81(3.14) | | n^2+2n= | | 8.5-3z=-8 | | 14x+1=5x-7 | | 13x-15=0 | | x+6=36+4 | | [3x+6]-9=3 | | 5x-2y=-2 | | -4(6+n)+4=38 | | x(5x-12)=9 | | [3x+6]-9= | | -x^2+28-9=0 | | 4x-5y=-25 | | -2(x-4)=2x-4(-2-3x) | | 4(2x-3)=10x | | 3x=103 | | 3(x+4)+2(5x-1)= | | 9z=17-26 | | 3x+12+6+10x-2= | | 18+16=234 | | 16(x-3)=-34 | | 7(3d-5)= | | 4(2b+2)-2=-14+3b | | .75y+2=-10 |